Is a Whole School Approach to Inclusion Really Meeting the Needs of All Learners? Home-Schooling Parents' Perceptions - Chris Forlin; Dianne Chambers (MDPI AG, 2023)
This paper examines issues impacting parental choice for home-schooling in one state in Australia. Data were collected from 99 parents home-schooling at least one child during the 2022 academic year. Utilizing the newly developed Parent Perceptions of Home-Schooling scale, consideration was given to proactive and reactive reasons perceived by parents as impacting their decision-making. Proactive reasons consisting of philosophical beliefs and needs of the child were cited more frequently by parents who had always home-schooled their child. Reactive reasons were mostly employed to confirm parent decisions to remove a child from school due to concerns regarding the school, the child, and the needs of parents. A range of school, child, and parental issues, and different child needs were identified as impetus for home-schooling learners with and without a diagnosed disability or an additional learning need. Discussion centers around whether current whole school approaches to inclusion are addressing the needs of all learners and parents, as perceived by this cohort. By gaining a better understanding of parental reasons for withdrawing their children with specific educational needs from regular schooling, this study is significant as it highlights a range of pertinent school-based issues to be considered to ensure effective inclusion for all.